Perlindungan Hukum bagi Pelaku Usaha terhadap Risiko Pengembalian Barang (Return) dalam Sistem Cash On Delivery Ditinjau dari Kitab Undang-Undang Hukum Perdata dan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Khaza Naturrachma; Nuzul Rahmayani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The Cash on Delivery (COD) system is one of the payment methods frequently used in online buying and selling transactions, where consumers pay for ordered products upon receipt of the goods. Although it provides convenience, this system often causes problems, especially related to transaction cancellations by consumers after the delivery process has been carried out by business actors. This research examines how the regulation and allocation of risk for goods return in the COD system according to the Civil Code and the forms of legal protection provided to business actors against the risk of goods return in the COD system according to Law Number 8 of 1999 concerning Consumer Protection. The method used in this research is normative, supplemented by literature study results such as legislation. The results show that the Civil Code recognizes the concept of risk as a legal consequence related to the possibility of losses on the object of the agreement, and legal protection for business actors is divided into preventive legal protection and repressive legal protection.